(untitled) (Research, Society and Development, 2021)
Violence against children is characterized by the presence of physical, sexual, emotional and psychological abuse, which can affect their development. That said, this article aims to discuss, specifically, sexual violence against the infant, covering aspects related to the aggressors, to the consequences implied for the victims, thus highlighting the factors that interfere in their process of maturation. Finally, it discusses issues related to the protection of victims and their treatment, in order to avoid worsening printed traumas. This is a bibliographic review study, for which research was carried out on articles, books and booklets that covered the delimited subject. We identified as results that in the midst of so many losses, the result of stressful events and of a threatening nature, it is worth mentioning that the child victim of sexual abuse, with or without penetration, has its maturation process and brain organization threatened. The lack of new studies, research and bibliographies in general that deal with the topic was identified, in addition to few methods of preventive dissemination. We concluded, at the end of the study, that sexual abuse against the child will generally be able to inscribe on the victim several marks, often as a result of the physical and psychological violence associated with the event, since the subject who suffers the abuse is not yet prepared - from a physical, emotional and psychological point of view - for the sexual act.